PARADIGMA BARU MICROFINANCE: PERGESERAN DARI SUBSIDI KE KOMERSIALISASI - Firmansyah, Rheza Aditya Fajar; Mardiyah, Dien (JURNAL LENTERA BISNIS, 2026)
This study discusses the paradigm shift in microfinance from a subsidy-based poverty lending approach toward a sustainable and commercial financial systems approach. Using literature review methods based on Marguerite S. Robinson (2001) and related works such as Yunus (1999), Morduch (1999), and Yaron dkk. (1998), this paper explores the drivers behind this transformation. The case of Bank Rakyat Indonesia’s (BRI) Unit Desa demonstrates the success of a commercially viable microfinance model in reaching the poor sustainably without reliance on government subsidies. The findings highlight that professionally managed, market-oriented microfinance can enhance financial inclusion, empower local economies, and strengthen the resilience of low-income communities. Thus, commercialization of microfinance does not diminish its social mission but rather expands its impact through institutional sustainability and financial innovation